Gestión en el manejo de los residuos sólidos en la municipalidad distrital de Punchana- Iquitos- Maynas, Loreto -2021 - Arce Escobar, Vely Jackeline (2021)
This research was carried out in the District Municipality of Punchana, in the Environment area, in order to identify the level lof performance of the office of the environment area of the District Municipality of Punchana, regarding the management in solid waste. According to the obtained results, the production of household solid waste in Punchana district reaches 0.62kilograms per person-day, which projected to the entire population of this district, could generate 56.49 tons/day 1694,98 tons/month and 20339.77 tm/year. 78.42% of the solid waste generated in the district of Punchana is usable, a volumen considered high, 15.31% not usable and 6.27% dangerous. In the Planning area, the highest number of responses was 41, which corresponds to the SOMETIMMES categoty. In the Organization area, the highest number of responses was 36, which corresponds to the ALMOST ALWAYS category. In the Direction area, the highest number of responses was 52, which corresponds to the SOMETIMES category. In the Control area, the highest number of responseswas 39, which corresponds to the SOMETIMES category. The general result shows a percentage of 39% (sometimes) which implies that the perception regarding the level lof performance of the environment area needs some corrections to notably improve management.